Changes in markers of subclinical atherosclerosis in patients with familial hypercholesterolemia treated with evolocumab: a prospective cohort study. (25th November 2020) - Calcaterra, I; Di Minno, A; Gentile, M; Tripaldella, M; Buonaiuto, A; Forte, F; Di Taranto, M.D; Giacobbe, C; Iannuzzo, G; Rubba, P.O.F; Di Minno, M.N.D
Abstract: Background: PCSK-9-i demonstrated efficacy in cholesterol reduction and prevention of cardiovascular events. Purpose: Changes in lipid-profile, oxidative stress and subclinical atherosclerosis markers in patients with familial hypercholesterolemia (FH) during 12 weeks of treatment with PCSK-9-i. Methods: Patients with FH starting a treatment with Evolocumab® were included. TC, LDL-C, Lp(a), small dense LDL (assessed byLDL score), 11-dehydro-thromboxane (11-TXB2), 8-iso-prostaglandin-2alpha (8-iso-PGF2α), FMD, RHI and carotid stiffness were evaluated at baseline and after 12weeks of treatment. Results: 25 subjects were enrolled (52% males, mean age 51.5 years). At the 12-week, the median reduction was 38% for TC, 52% for LDL-C, 7% for Lp(a) and 46% for LDL score; 11-TXB2 and 8-iso-PGF2α were reduced of 18% and 17%, respectively. FMD changed from4.78%±2.27 to10.6%±5.89 (p<0.001), with RHI changing from 2.37±1.23 to 3.76±1.36 (p<0.001). Carotid stiffness changed from 8.8 (IQR: 7.0–10.4)m/sec to 6.6 m/sec (IQR: 5.4–7.5), p<0.001). At a multivariate analysis, changes in LDL score predicted changes in FMD (β=−0.846, p=0.015) in carotid stiffness (β=0.429, p=0.041), and in 8-iso-PGF2α (β=0.778, p=0.012). Conclusions: Small dense LDL reduction is related to changes in oxidative stress and in subclinical atherosclerosis markers in FH patients treated with Evolocumab®. Funding Acknowledgement: Type of funding source: None